2013
DOI: 10.1016/j.juro.2012.09.055
|View full text |Cite
|
Sign up to set email alerts
|

JTS-653 Blocks Afferent Nerve Firing and Attenuates Bladder Overactivity Without Affecting Normal Voiding Function

Abstract: Our findings suggest that TRPV1 is involved in bladder overactivity via afferent nerve activation but it is not associated with normal voiding function. A TRPV1 antagonist would be a useful drug for bladder overactivity with a different pharmacological profile than antimuscarinic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…9) was reported to ameliorate PNH pain in rodent models (Kitagawa et al, 2013a). In the rat bladder, JTS-653 suppressed overactivity without affecting normal micturition (Kitagawa et al, 2013b). According to the company website, this compound is now in phase II clinical trials in Japanese patients with painful overactive bladder (www.jt.com/ investors/results/S_information/pharmacauticals/pdf/ P.L.20220207_E.pdf).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…9) was reported to ameliorate PNH pain in rodent models (Kitagawa et al, 2013a). In the rat bladder, JTS-653 suppressed overactivity without affecting normal micturition (Kitagawa et al, 2013b). According to the company website, this compound is now in phase II clinical trials in Japanese patients with painful overactive bladder (www.jt.com/ investors/results/S_information/pharmacauticals/pdf/ P.L.20220207_E.pdf).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…The bladder phenotype of the TRPV1 knockout mouse is, however, less pronounced: these animals showed only mild spotty incontinence (Birder et al, 2002). Furthermore, TRPV1 antagonists did not alter micturition in naïve animals (Charrua et al, 2009a;Kitagawa et al, 2013b). When explaining these seemingly conflicting results, it should be kept in mind that neonatal capsaicin administration ablates not only TRPV1 but also other receptors coexpressed with TRPV1 on bladder afferents that may be involved in micturition.…”
Section: Transient Receptor Potential Channels As Therapeutic Targmentioning
confidence: 99%
“…Here, TRPV1 antagonists inhibit capsaicin-induced increases in pelvic nerve discharge and intravesical pressure in rats and are able to suppress bladder overactivity induced by resiniferatoxin and acetic acid (Charrua et al 2009;Kitagawa et al 2013b). In addition, TRPV1 antagonists have been demonstrated to be effective in reducing colonic hypersensitivity in rodents (Kiyatkin et al 2013;Wiskur et al 2010).…”
Section: Trpv1 Antagonists and Agonists In Vivomentioning
confidence: 99%
“…As an example, in one of the most recent reports the TRPV1 antagonist JTS-653 was shown to reduce afferent nerve firing, and micturition frequency in rats. Intravesical instillation of resiniferatoxin (RTX), an ultrapotent capsaicin analogue, significantly increased the number of electrophysiologically measured bladder afferent nerve impulses per second [41]. This increase of nerve discharge by RTX could be prevented when rats were administered JTS-653 intravenously 5 min prior to electrophysiological recording experiments.…”
Section: Transient Receptor Potential Cation Channel Subfamily V Membmentioning
confidence: 99%
“…Thus, the authors concluded that JTS-653 (or in general, TRPV1 antagonism) might be a therapeutic approach to treat OAB [41]. To the best of our knowledge, no TRPV1 antagonist has been tested clinically in regards to OAB and/or LUTS.…”
Section: Transient Receptor Potential Cation Channel Subfamily V Membmentioning
confidence: 99%